Newly developed apparatus for calibration of quadrupole mass spectrometer. (18th November 2016) - Meng, Dong; Yongjun, Cheng; Detian, Li; Wenjun, Sun; Lan, Zhao; Meiru, Guo; Yongjun, Wang; Huzhong, Zhang; Yanwu, Li; Gang, Li
Abstract: In this paper, a new calibration apparatus has been developed for calibrating quadrupole mass spectrometer (QMS) from 10 −8 Pa to 10 −2 Pa for He, N2 and Ar. Based on the apparatus, two calibration methods are introduced to generate standard pressure P i ′ (or P i ″) of lower than 10 −2 Pa, which are named as 'the SRG measurement method' and 'the CDG measurement method'. The SRG measurement method can generate a standard pressure range from 10 −8 Pa to 10 −5 Pa, and the CDG measurement method can generate a standard pressure range from 10 −5 Pa to 10 −2 Pa. A molecular flow condition is determined and a QMS is calibrated by the two methods using single gas and mixture gas. The gas flow through the small tube and orifice realizes molecular flow at an upstream pressure of less than 70 Pa. The sensitivities calibration results with the two methods agree well, and the difference is less than 3%. The sensitivity calibrated with single gas is different from that calibrated with mixture gas. Obtained results are roughly consistent with those of previous studies.